Analysis of User’s Acceptance of The Accrual-Based Financial Simda with Technology Acceptance Model (Tam) 3 Adapted Approach - Rusmana, Oman; Bawono, Icuk Rangga; Indriyani, Riza Uyun (Unand Press, 2018)
The purpose of this research is to analyze the user’s acceptance of the Accrual-Based Financial SIMDA by using Technology Acceptance Model 3 adapted approach. The research has 7 variables, namely: Result demonstrability (RES), Computer Playfulness (CPLAY), Perceived Enjoyment (ENJ) , Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Behavioral Intention (BI), and System Usage (USE). This research is a quantitative research held at the Local Government of Brebes. The method of gathering data is survey by distributing questionnaires to the respondents. The research uses proportionate stratified random sampling. A total of 108 questionnaires were distributed in this study, 106 questionnaires could be collected. The result shows that the System Usage (USE) is affected by three variables, namely: Behavioral Intention (BI), Perceived Usefulness (PU) and Perceived Ease of Use (PEOU). Behavioral Intention (BI) is affected by Perceived Usefulness (PU) and Perceived Ease of Use (PEOU). Perceived Usefulness (PU) is affected by Result Demonstrability (RES) and Perceived Ease of Use (PEOU). Meanwhile, Perceived Ease of Use (PEOU) is affected by the Computer Playfulness (CPLAY) and Perceived Enjoyment (ENJ). This research expected to provide a solution to the problems related to user acceptance of the Accrual-Based Financial SIMDA and to increase user acceptance.